ANALISIS TEKANAN PENDUDUK TERHADAP LAHAN PERTANIAN SAWAH DI KECAMATAN BATIPUH - Fitri Rahmadani; Ratna Wilis (JURUSAN GEOGRAFI FIS UNP, 2021)
This research was conducted to see how variations in population pressure on paddy fields, variations in the carrying capacity of paddy fields and to determine the optimum population size in Batipuh District. This type of research is descriptive quantitative. This research was conducted in Batipuh District, carried out from September to October 2020. The data analysis technique was obtained through the analytical tool used to calculate population pressure using Prof. formula. Otto Soemarwoto model II. The results showed that Batipuh District had experienced population pressure (TP <1). The highest value of population pressure in Batipuh District was in the village of Bungo Tanjung (106.8), while the lowest value was in the village of Sabu (39.9). The results of the analysis of the carrying capacity of the land show that there are 5 villages that are able to meet the food needs of their residents properly, namely Andaleh, Sabu, Batipuh Baruah, Pitalah, Bungo Tanjung. There are 2 nagari that are in class II classification, namely the Batipuh Ateh village and the Gunung Rajo village. Nagari with class III classification is only found in Tanjung Barulak village, which means that the village has not been able to provide adequate food. Nagari whose population has not exceeded the optimum limit consists of 7 nagari, namely; nagari Bungo Tanjung, Pitalah, Gunung Rajo, Batipuh Baruah, Batipuh Ateh, Sabu and Andaleh. Nagari whose population has passed the optimum limit is the village of Tanjung Barulak. Key Words: Population Pressure, Land Carrying Capacity, Optimum Population